QoS ontology for service selection and reuse - Chhun, Sophea; Moalla, Néjib; Ouzrout, Yacine (Journal of intelligent manufacturing, 2016)
Web service technologies become popular in software development in all sectors. Variety services related standards are defined but they still have limitations to represent the services such as the service registry does not support the Quality of Service (QoS) properties, web service description language does not allow specifying the QoS properties and there is no common ontology’s structure to store services. Our research aims to enhance the representation of services to assist the service selection and composition process in order to reduce the development costs. The existing resources are analyzed to define a web service ontology (WSOnto). Furthermore, a service selection algorithm is proposed to validate the proposed WSOnto. It considers the multiple criteria of inputs such as: context, functional and non-functional properties of services. The WSOnto and a service selection algorithm are studied to assist the re-engineering of business processes from users’ designed business processes.